Feasibility Analysis of Capacity Building at CV X Bintaro Branch - Fatahillah Ramdhan, R. Adji; Susanto, Sani; Rian Praktikto, Franciscus (Ann Publisher, 2024)
CV X is a company engaged in beauty services such as nail and eyelash treatment. CV X has a problem: a lack of salon capacity due to the high customer demand. This caused lost sales of IDR 188,597,000 in 2022 because customers were rejected when they wanted to book due to full capacity. Therefore, the owner of CV X plans to increase the capacity of the Bintaro branch to minimize the occurrence of lost sales, which can cause significant losses. To improve this capacity, an analysis is needed to precede it so that CV X can determine whether this capacity-building plan is feasible from various aspects to minimize failures. The feasibility analysis of this capacity building will be carried out on five main determining aspects: market and marketing, operational, legal, financial, and environmental. The market and marketing aspects discuss the company's competitive strength, the potential for market growth, and marketing strategies. The operational aspect discusses the current capacity, plans to increase capacity and layout, and the number of human resources needed. The legal aspect discusses the best form of business entity and the necessary documents and requirements. The financial aspect discusses the feasibility of investment with projected demand estimates, HPP calculations, income statements, and cash flow statements. It assesses feasibility based on Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period indicators. After the research activities were conducted, the results were obtained that the market aspect was feasible because it had a significant market share and knew the best way to maximize the potential market share. The operational aspect is feasible because it knows the layout plan and the details of the number of workers needed. The legal aspect is feasible because it meets the legal requirements and knows the best form of business entity. The financial aspect is feasible because the projected value generated in the economic calculation exceeds all the indicators used: the NPV value of Rp3,139,234,978, IRR of 219%, and Payback Period of 0.66. The environmental aspect is said to be feasible because it can handle all the waste appropriately produced so that it does not pollute the surrounding environment.